Implementasi Inovasi Kebijakan Smart City di Kota Tanjungpinang - Batuara , Lis Veronica; Sasmita, Intan; Silitonga, Theresia (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2022)
This research refers to the concept of exploring the existence of a smart city arrangement that can play a role in facilitating the public to obtain information quickly and precisely. In Tanjungpinang City itself, the Smart City concept has been introduced since 2017, and Tanjungpinang is also included in the ambition to achieve 100 Smart Cities in Indonesia, which has been targeted from 2017-2020. Based on the Instruction of the President of the Republic of Indonesia No. 3 of 2003 concerning the National Development Strategy Policy for Government Development. Through the development of e-government, management systems and work processes are arranged in the government environment by optimizing the use of information technology. So in the application of the smart city concept, there are six indicators that need to be considered for development, namely Smart Governance, Smart Branding, Smart Economy, Smart Living, Smart Society, Smart Environment. This research uses qualitative method with descriptive research type.